Autologous stem cell transplant is an effective therapy for carefully selected patients with AL amyloidosis: experience of a single institution. (25th November 2013) - Jimenez‐Zepeda, Victor H.; Franke, Norman; Reece, Donna E.; Trudel, Suzanne; Chen, Christine; Delgado, Diego H.; Winter, Andrew; Mikhael, Joseph R.; Tiedemann, Rodger; Kukreti, Vishal
Summary Autologous stem‐cell transplant has been widely used to treat patients with AL amyloidosis. However, transplant‐related mortality rates are high, and a recent randomized trial suggested that non‐transplant regimens produced comparable results with less toxicity. In order to define the role of patient selection in stem cell transplantation, we evaluated 78 consecutive AL amyloidosis patients transplanted at our centre. Transplant‐related mortality occurred in 11·5%. Complete haematological response and organ response were achieved in 56% and 60%. Median overall survival was significantly lower for patients with brain‐type natriuretic peptide (BNP) >300 pg/ml (17·5 months vs. not‐reached) (P = 0·0004), troponin‐I >0·07 ng/ml (13·5 months vs. not‐reached) (P = 0·00001) and those not achieving a complete haematological response (88 months vs. not‐reached) (P = 0·0345); high BNP and troponin‐I were the most important predictive factors in a multivariate analysis. Based on this study, patients with BNP <300 pg/ml and/or normal levels of troponin‐I should be considered transplant candidates.